Caracterización fisicoquímica y espectrometría ultravioleta visible del flavonoide aislado de Vitex pseudolea Rusby (paliperro) y su similitud filogenética con vitexina - Saboya Vela, Ibony (2022)
The purpose of the study was to achieve the isolation and purification of Vitexin from Vitex pseudolea Rusby, which is the active principal present in several species of the genus Vitex due to its phylogenetic properties that characterize it as belonging to a monophyletic family. The sample was collected in the town of Tamshiyacu, District of Sgto. Fernando Lores Tenazoa, Maynas, Loreto, the heartwood was taken to sawdust for extraction with solvents. The active principle was characterized by determining its physicochemical properties and by UV-Visible spectrometry. 2.352 g of vitexin were obtained, the melting point was 204 ° C., Soluble in methanol, ethanol and hot water. The colored tests were positive for flavonoid, the molecular weight calculated by the Rast method gave 432.37 g / mol ± 0.049. The Rf values were made with various solvent mixtures, using a mixture of ethyl acetate: butanone: formic acid: water, the Rf value gave 37, with benzene: methanol: butanone gave a value of 68, finally, using as solvent elution: water: ethanol: butanone: acetyl acetone gave a value of 25. The maximum wavelength values in UV / visible using MeOH as the spectrometric shift reagent gave the following 270, 302 Sh, 366 nm. and in a mixture of MeOH: AlCl3: HCl gave 278, 303, 343, 383 nm. These values fully coincide with those reported by the literature thus it is concluded that the component isolated from the stem of Vitex pseudolea Rusby is Vitexin.